Laryngeal afferent modulation of swallowing interneurons in the dorsal medulla in perfused rats. (9th September 2019) - Fuse, Shinya; Sugiyama, Yoichiro; Hashimoto, Keiko; Umezaki, Toshiro; Oku, Yoshitaka; Dutschmann, Mathias; Hirano, Shigeru
Abstract : Objectives: The purpose of this study was to investigate the influence of laryngeal afferent inputs on brainstem circuits that mediate and transmit swallowing activity to the orofacial musculature. Methods: Experiments were performed on 19 arterially perfused juvenile rats. The activities of swallowing interneurons in relation to their respective motor outputs in the hypoglossal and vagus nerves were assessed during fictive swallowing with or without concurrent laryngeal sensory stimulation at intensities of 20, 40, and 60 μA. Results: The hypoglossal nerve activity was gradually enhanced with increasing intensity of the sensory stimulation, while the vagus nerve activity was not altered. The activities of various interneurons were modulated by the laryngeal stimulation, but more than 50% of the recorded neurons were inhibited by the stimulation. Some interneurons demonstrated no obvious change in their discharge rates with laryngeal sensory stimulation during fictive swallowing. Conclusion: Laryngeal afferent inputs partially modulated the swallowing motor activity via enhanced or suppressed activities of the swallowing interneurons, while the essential motor pattern underlying the pharyngeal stage of swallowing remained basically unchanged. Thus, the output patterns of the complex sequential movements of swallowing could be basically predetermined and further adjusted according to sensory information related to the properties of the ingested food by a swallowing central pattern generator. Level of Evidence: NA Laryngoscope, 130: 1885–1893, 2020